Impact of Brand Placements in Bollywood Movies – Researching The Youth - Narula, Divya (2009)
This research explores how brand placement in Bollywood movies is perceived by the viewers and to what extent are they affected by these placements. Brand Placements in the Bollywood industry has grown rapidly over the last few years. In this age of global advertising, marketers are looking for new techniques of advertising to promote their brands to a larger audience. This research comprises of the views of Indian students in New Delhi and NCR. This paper will review the literature on brand placements, growth of brand placements in the Bollywood industry, the views and the perception of viewers regarding brand placements. The paper then discusses the brand placements in terms of the youth in India which is divided mainly into two themes, effectiveness of brand placements and the perception of brand placements in the minds of the youth of India. By investigating these subjects together, the research will be able to highlight the scenario of brand placements in the Bollywood industry. Lastly, bringing together the theoretical and practical findings, the final conclusion of the research will be discussed with its limitations and further areas of research.